2017
DOI: 10.1177/1076029616683046
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Dose Model for the Prediction of Stable Maintenance Dose in Indian Patients

Abstract: The main aim of this study was to screen various genetic and nongenetic factors that are known to alter warfarin response and to generate a model to predict stable warfarin maintenance dose for Indian patients. The study comprised of 300 warfarin-treated patients. Followed by extensive literature review, 10 single-nucleotide polymorphisms, that is, VKORC1-1639 G>A (rs9923231), CYP2C9*2 (rs1799853), CYP2C9*3 (rs1057910), FVII R353Q (rs6046), GGCX 12970 C>G (rs11676382), CALU c.*4A>G (rs1043550), EPHX1 c.337T>C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…This could be explained by the presence of confounders and the study design being a retrospective audit without any scope for follow-up. On the other hand, a controlled prospective study by Gaikwad et al 29 in western Indian patients on warfarin demonstrated that five variables ( VKORC1 –1639 G>A, CYP2C9 *2, CYP2C9 *3, age, and diet) were significantly associated with warfarin response in an univariate analysis. After stepwise multiple regression analysis with these five variables, the developed prediction model was found to be explaining approximately 67% of warfarin dose variability (R 2 = 0.67).…”
Section: Discussionmentioning
confidence: 98%
“…This could be explained by the presence of confounders and the study design being a retrospective audit without any scope for follow-up. On the other hand, a controlled prospective study by Gaikwad et al 29 in western Indian patients on warfarin demonstrated that five variables ( VKORC1 –1639 G>A, CYP2C9 *2, CYP2C9 *3, age, and diet) were significantly associated with warfarin response in an univariate analysis. After stepwise multiple regression analysis with these five variables, the developed prediction model was found to be explaining approximately 67% of warfarin dose variability (R 2 = 0.67).…”
Section: Discussionmentioning
confidence: 98%
“…To evaluate the effects of food, we compared warfarin dosages between children partly receiving milk powder and those with normal diet, and found the former required lower doses than the latter (1.203 ± 0.439 mg vs. 1.957 ± 0.769 mg, P = 0.004); however, the former cases were all infants. A study of 300 adults showed vegetarian or accidentally nonvegetarian patients intake lower warfarin doses than non-vegetarians [ 17 ]. Besides, diverse warfarin indications require different daily doses.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithms also predict extreme doses less efficiently (i.e., low or high daily warfarin doses) [ 15 , 24 ]. Algorithms designed for African-American, Indian, and Chinese patients have been developed but have not been tested in clinical trials [ 25 , 26 , 27 ].…”
Section: Warfarin Pharmacology and Pharmacogeneticsmentioning
confidence: 99%